2018
DOI: 10.18632/oncotarget.23916
|View full text |Cite
|
Sign up to set email alerts
|

Dual trigger of triptorelin and HCG optimizes clinical outcome for high ovarian responder in GnRH-antagonist protocols

Abstract: In this paper, a retrospective cohort study was conducted to the high ovarian responders in GnRH-antagonist protocols of IVF/ICSI cycles. The purpose of the study is to investigate whether dual triggering of final oocyte maturation with a combination of gonadotropin-releasing hormone (GnRH) agonist and human chorionic gonadotropin (HCG) can improve the clinical outcome compared with traditional dose (10000IU) HCG trigger and low-dose (8000IU) HCG trigger for high ovarian responders in GnRH-antagonist in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…We could not find any report in the literature that advocates for the use of 2,000 IU hCG for ovulation trigger. Such low doses are only used for dual trigger with GnRh analogs to optimize clinical outcomes for high ovarian responders in GnRH-antagonist protocols [22]. Most cases of FEFS can be avoided by confirming that the patient self-administered her prescribed hCG dose by measuring the amount of β-hCG in her blood the morning after the hCG was administered, as is the practice in our unit and as advocated by others [9].…”
Section: Discussionmentioning
confidence: 94%
“…We could not find any report in the literature that advocates for the use of 2,000 IU hCG for ovulation trigger. Such low doses are only used for dual trigger with GnRh analogs to optimize clinical outcomes for high ovarian responders in GnRH-antagonist protocols [22]. Most cases of FEFS can be avoided by confirming that the patient self-administered her prescribed hCG dose by measuring the amount of β-hCG in her blood the morning after the hCG was administered, as is the practice in our unit and as advocated by others [9].…”
Section: Discussionmentioning
confidence: 94%
“…Previous retrospective studies indicate that dual trigger can reduce the OHSS rate in predicted high responders [ 32 , 33 ]. Because most trials included in our study enroll women with a moderate response, whether the dual trigger is more applicable in high or moderate or poor responders requires further confirmation [ 10 , 32 , 33 ]. Additionally, no consensus has been reached towards the best dose of GnRH agonist and hCG in the dual trigger treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A bulk of evidence have suggested that dual trigger haveseveralsigni cant advantages over hCG or GnRHa protocol,such as better luteal phase supportand lower risk of OHSSin normal and/or high respond patients [6][7][8]. More importantly, some reports showed that dual trigger may improve oocyte retrieval and maturation, cultural outcome, as well as embryo implantation in subjects with normal ovarian reservation [9,10].…”
Section: Introductionmentioning
confidence: 99%